Efficient cardiomyocyte differentiation of induced pluripotent stem cells on PLGA nanofibers enriched by platelet‐rich plasma. (8th November 2020) - Torabi, Maryam; Abazari, Mohammad Foad; Zare Karizi, Shohreh; Kohandani, Mina; Hajati‐Birgani, Nazanin; Norouzi, Sara; Nejati, Fatemeh; Mohajerani, Alireza; Rahmati, Tahereh; Mokhames, Zakiye
Abstract : Regeneration and restoring the function of the myocardial‐infracted hearts have been one of the constant challenges in medicine. Recently, tissue engineering, using biocompatible substrates and stem cells, holds a real promise to solve these problems. Herein, poly(lactic‐co‐glycolic acid) (PLGA) nanofibers and platelet‐rich plasma (PRP) enriched PLGA nanofibers (PLGA‐PRP) were fabricated by electrospinning. Scanning electron microscopy (SEM) demonstrated that fiber diameters in PLGA scaffolds with and without PRP were in the range of 500 ± 280 nm and fibers were also bead free, smooth, in random orientation, and with interconnected pores. During culture of the human‐induced pluripotent stem cells (iPSCs) on the nanofibrous scaffold, further differentiation of the iPSCs to cardiomyocytes was detected in PLGA‐PRP nanofibers compared to the PLGA. This improvement in differentiation potential was evaluated at the morphological, molecular gene, and protein expression levels using SEM, real‐time reverse transcription‐polymerase chain reaction (RT‐PCR), and immunocytochemistry, respectively. The results obtained in this study highlighted the significance of natural growth factors present in the artificial scaffold applied in cardiac tissue engineering according to the improvements in cell‐biomaterial interactions. Taken together, our result indicated that PRP‐incorporated PLGA could be considered as a great potential candidate to use for engineering suitable myocardium replacement constructs.